A thermoelectrical parameter investigation using pyroelectric techniques: Application on Mylar. Issue 2 (17th February 2017) - Mami, A.; Bennaji, N.; Mellouki, I.; Yacoubi, N.
ABSTRACT: The pyroelectric methods have been recognized as a reliable and useful tool for the measurement of the thermoelectrical properties of Mylar layer. Using a new approach of theoretical models of photopyroelectric and electropyroelectric methods, it is possible to deduce thermal diffusivity, thermal conductivity, and electrical impedance of the given polyester film. The experimental results were found to be in agreement with the literature and the impedance analyzer values.